The Effectiveness of Character Strengths-Based Peer Counseling in Fostering Psychological Well-Being in Islamic Boarding Schools - Muslikah, Muslikah; Sugiharto, Dwi Yuwono Puji; Mahfud, Ashari; Sofyan, Afriyadi; Endalan, Lailawati Madlan; Prabawa, Abi Fa’izzarahman (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2026)
Low psychological well-being and elevated help-seeking behaviors among students in Islamic boarding schools underscore the necessity for effective psychological support systems. This study assesses the effectiveness of a character strengths-based peer counseling intervention in enhancing students' psychological well-being within Islamic boarding school settings. Grounded in the principles of positive psychology and aligned with Islamic educational values, the intervention emphasizes five core character strengths (gratitude, hope, zest, curiosity, and love) delivered through a peer counseling framework. Employing a quasi-experimental pretest-posttest control group design, the study involved 81 first-year students (ages 13-17) from three pesantren in Semarang, randomly assigned to experimental (n = 45) and control (n = 36) groups. The Psychological Well-Being Scale (Ryff, 1989) was used to measure six dimensions of well-being. Data were analyzed via Two-Way ANOVA to evaluate the intervention's impact over time. Results indicated significant improvements in psychological well-being within the experimental group (p < .01), with a notable post-test mean score increase of 13.53 points, interaction effect with η²p = 0.049. This value approaches the moderate category. These findings substantiate that character strengths-based peer counseling is an effective and culturally appropriate intervention for promoting mental health in faith-based educational environments. The study contributes to applying positive psychology in non-Western contexts, emphasizing the potential of peer-led models to enhance adolescents' emotional resilience, interpersonal relationships, and religious character development. The study's limitations and potential directions for future research are also discussed to improve the generalizability and sustainability of the intervention.